The Pentateuch as narrative : a biblical-theological commentary - Sailhamer, John H. (Grand Rapids, MI : Zondervan, 1992)
Includes bibliographical references.
Includes bibliographical references.
Keywords: Bible. -- commentaries; Narration in the Bible